Cooking on Slovene national television during socialism - Tominc, Ana (Družboslovne razprave, 2015)
This article gives a brief historical overview of cooking programmes broadcast on TV Ljubljana between 1960 and 1990 that were mainly produced in Slovenia. From the famous chef Ivan Ivačič in the early 1960s through "Vegeta's kitchen" in the 1970s to a children's cooking show, Lonček, kuhaj Little pot, cook! in 1990, I analyse the contents of these shows and demonstrate their thematic variation. I also place them in their historical context, especially in terms of socialist television. Cooking shows, which were not only a source of knowledge about new equipment, ingredients and cooking techniques, also revealed to the audience during socialism a different lifestyle, tastes and manners, making television one of the important contributors to the idea of the community, either as a class or nation. Despite this, compared to contemporary cooking shows, the genre of the time remains directed towards education, a feature generally not dissimilar to cooking shows in non-socialist contexts.
Keywords: Television cooking shows; Televizijske kuharske oddaje; Socialism; Socializem; Education; Izobraževanje; televizijske oddaje; kuhanje; Slovenia; Slovenija